Marketing Theory Evolution and Interpretations - Pranulis, Vytautas Pranas; Abromaitytė-Sereikienė, Laima (Ekonomika, 2003)
The problem, which is surveyed in this article, includes the lack of scientific publications on the theme of marketing theory’s evolution here in Lithuania (this causes the problems of misunderstanding between marketing specialists). Solving the problem is based on the analysis of the main schools of marketing theory: noninteractive-economic, interactive-economic, nontineractive-noneconomic interactive-noneconomic schools of marketing. Considering that non interactive- economic and interactive-economic schools made the biggest influence to the evolution of marketing theory - a lot of ideas from these schools are nowadays used practically - the biggest part of this article is assigned to these two trends of theory evolution. There arc presented the main theorists of these schools, the trends, which they researched, main ideas, for example, such as classification system of goods, classification of marketing functions, structure of marketing channel, marketing mix, segmentation, etc.The comparison of ideas, which belongs to different marketing schools of thought, let make better acquaintance with main ideas of marketing theory, learn about the authors, to understand the origin of today’s marketing theory content, structure and logic. In spite of the fact that the main theories, which are looked over in this article, already are investigated in the textbooks of marketing, but the discussions on these theories aren’t still over. That’s why analysis and better understanding of these theories can encourage the further development of marketing thought, especially in Lithuania, where marketing theorists make the first steps.The article proves that further analysis of marketing theory evolution is actual to Lithuania not only for the misunderstanding problems between specialists, but also for the reason which shows that Lithuania still collide with the same problems, which occurred in the birth of some marketing theory schools (the problem of agriculturists).